Ground based bistatic scatterometer measurement of rice crop at C-band in the specular direction - Vishwakarma A.K.; Prasad R.; Gupta D.K.; Kumar P.; Mishra V.N. (My University, 2025)
The objective of this study is to investigate the bistatic scattering response of rice crop in the specular direction with the azimuthal angle (=0) using bistatic scatterometer system at C-band. A rice crop bed of area 4×4 m2 was prepared at the outdoor field behind the Department of Physics, IIT (BHU), Varanasi for a ground based bistatic scatterometer measurement during different growth stages at co-polarizations (HH and VV) and cross polarization (VH) for the incidence angle 20°-60°. The crop growth variables such as fresh biomass (FBm), vegetation water content (VWC), leaf area index (LAI) and plant height (PH) were also measured at the time of each bistatic scatterometer measurement of the rice crop. The correlation analysis were carried out between the bistatic scattering coefficient and rice crop growth variables at all the incidence angle and polarizations (HH, VV and VH) to select the optimum angle of incidence and polarization for the measurement of rice crop using bistatic scatterometer system at C-band in the specular direction. © 2018 IEEE.